Promoting senggi folktales as media of contextual teaching learning in Papua - Suhartawan, Vina Vania; Yektiningtyas, Wigati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
In EFL class, some students mostly struggle to comprehend reading since the material is not contextually suitable for their needs. Senggi folktale is one of the media to teach reading skill contextually and is now forgotten by Papuan youngsters. This study aimed to explore how to engage students to read narrative text and promote the teaching of reading by using Senggi folktales. This descriptive-qualitative study took place in Keerom, Papua, Indonesia between July and September 2015. There were students of Junior High School, 1 Junior High School teacher, 1 ex-elementary school teacher, 1 tribal chief, and 2 elders as the informants. The data were collected by using observation, interview, and FGD (Focus Group Discussion). The study discovered that students could effectively and enthusiastically learn the social function, generic structure, and linguistic features of the contextual reading material, Senggi folktale. They also indirectly do cultural heritage preservation and get the good socio-cultural values revealed in Senggi folktale.